If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 2x + 3 = 0 Reorder the terms: 3 + 6x + 2x = 0 Combine like terms: 6x + 2x = 8x 3 + 8x = 0 Solving 3 + 8x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 8x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 8x = 0 + -3 8x = 0 + -3 Combine like terms: 0 + -3 = -3 8x = -3 Divide each side by '8'. x = -0.375 Simplifying x = -0.375
| 7*x^2+84=0 | | 2(3+7x)-(1+15x)=2 | | y=1-8x | | -4p-6q-5= | | x=3y-4 | | 3a+5b+4+6a= | | (4x+51)= | | 2x+3x+4+4x= | | 6y+13+5y+2=180 | | -4x-7=3(2-x) | | -21x-29x=-56 | | 8x+5y=25 | | 3x+4x+5y= | | Mn+4m+6n+2mn= | | 4b-100=-6 | | 7x-2=6x+25 | | 0.2(50)+0.8r=0.4(50+r) | | 3x+(5x+2)=26 | | -2a+3a+5b= | | 19x-8x=-54 | | 5*x^2+45=0 | | 3(m+5)-1+2m=5(m+2) | | x*x+5=104 | | 18+6g=12g | | 8b-7b+1-b=9b-9-9b | | -35=7(2-8) | | 10y-18=9y+11 | | -2+5t-9=3(t-4)-5 | | 64=2n | | 7x^7=8888 | | 5(c+3)=3(c+9) | | 7(p-2)+p=2(p+2) |